Polysaccharide building blocks : a sustainable approach to renewable biomaterials - Habibi, Youssef; Lucia, Lucian A. (Hoboken, New Jersey : Wiley, 2012)
'This book is an archival reference for the evolving field of biomaterials and their applications in society, focusing on their composition, properties, characterization, chemistry and applications in bioenergy, chemicals, and novel materials and biomaterials. It has broad appeal due to the recent heightened awareness around bioenergy and biomass as potential replacements for petroleum feedstocks. The book is divided into three parts: cellulose-based biomaterials, chitin and chitosan biomaterials, and hemicelluloses and other polysaccharides. Each chapter addresses a separate biomaterial, discussing its chemical, physical, and biological attributes, and hones in on each compound's intrinsic tunability for numerous chemical transformations. In the current quest for a'green' economy and resources, this book will help inspire scientists towards novel sources for chemicals, materials, and energy in the years to come'--
Includes bibliographical references and index.
Keywords: Polysaccharides; TECHNOLOGY & ENGINEERING / Material Science